Estimation of fertility rates for Bayelsa state; using brass p/f ratio technique and gompertz relational model (2011)
The aim of this paper is lo examine fertility rate in the study area. The estimates presented in this research were sampled from secondary data extracted from records of three general hospitals in the three eco zones of the State using the Brass and Gompertz methods. From the analysis, it was observed that the estimated mean parities rise steadily with age reaching the peak in both methods. This observation is in line with the international standards that "data on lifetime fertility by the ages of women from most developing countries show that it rise steadily with age, reaching a maximum in the 45-49 age groups. " The estimated total fertility rates obtained from both methods in the State lies within the estimates reported for Nigeria. The study further show that fertility rate in the study area is high and varies relatively among the sampled zones. Since majority of the rural dwellers lack knowledge of family planning and with the absence of primary health care services, planners and policy makers in the health sector should formulate programs aimed at bringing these services closer to the people so as to dissuade them from child mortality. Furthermore. enlightenment campaigns should be put in place to educate them on the use of contraceptive and the importance of birth control.